FIELD TEST OF THE INDIGENOUS MICROBES FOR OIL RECOVERY, LEDOK FIELD, CENTRAL JAVA - A. Yusuf; S. Kadarwati; S.W. Pratomo (Testing Center for Oil and Gas LEMIGAS, 2002)
After selecting several old wells in Cepu, then well LDK-132 was chosen for implementing MEOR technology using